THE ROLE OF PARLIAMENTARISM IN PROTECTING WOMEN'S RIGHTS AND INTERESTS IN THE REPUBLIC OF BELARUS (EUROPEAN AND ASIAN LAW REVIEW, 2023)
The article is devoted to determining the role of the political and legal institution of parliamentarism in protecting the rights and interests of women and promoting them in the system of governance. The article draws attention to the fact that the principles of gender equality are enshrined in the Constitution of the Republic of Belarus, the Electoral Code, the laws "On Political Parties", "On Public Associations", "On Trade Unions", "On Local Government and Self-Governance in the Republic of Belarus", etc., but the system of power in the Republic of Belarus is a "gender pyramid". Today the problem of women's full representation in the higher authorities is actualized. The author considers the possibilities of the House of Representatives of the National Assembly of the Republic of Belarus as a legislative and representative body and the All-Belarusian People's Assembly as the highest representative body in promoting the ideas of gender equality. Attention is paid to the increase of women parliamentarians in the House of Representatives and the number of women candidates in parliamentary elections (from 2000 to 2019). Special attention is paid to the peculiarities of civil society in the Republic of Belarus: the activities of political parties, trade unions, the Belarusian Union of Women, and local self-government bodies to protect the rights, interests, and expand the socio-political influence of women are analyzed. The development of youth parliamentarism is considered among the promising directions in promoting ideas of gender equality.
Keywords: Republic of Belarus; parliamentarism; gender equality; parliament; civil society